Usefulness of intestinal real‐time virtual sonography in patients with inflammatory bowel disease. Issue 10 (7th May 2019) - Kawai, Shoichiro; Iijima, Hideki; Shinzaki, Shinichiro; Hiyama, Satoshi; Yamaguchi, Toshio; Araki, Manabu; Iwatani, Shuko; Shiraishi, Eri; Mukai, Akira; Inoue, Takahiro; Tsujii, Yoshiki; Hayashi, Yoshito; et al.
Abstract: Background and Aim: Transabdominal ultrasonography (US) examination for the intestine is often difficult, and its precedence for intestinal examination depends on accessibility to experienced ultrasonographers. Real‐time virtual sonography (RVS) assists examination of US as a fusion method by synchronizing US images with pre‐captured computed tomography or magnetic resonance images. We aimed to evaluate the feasibility to use RVS for the examination of the intestine. Methods: The time to scan three parts of the intestine was compared between conventional US and RVS in seven participants without intestinal diseases. Whether RVS accurately synchronized US images with reference images of intestinal target lesions was judged in 20 patients with inflammatory bowel disease. Results: Examination time to scan the ascending colon and the ileocecum using intestinal RVS was significantly shorter than that using conventional US alone (36.7 vs 50.0 s [ P = 0.0313] and 35.4 vs 66.4 s [ P = 0.0156], respectively) in participants without intestinal diseases. Well‐synchronized US images of the intestinal lesions, such as stenosis, with reference computed tomography/magnetic resonance images were obtained by RVS in all the lesions in the fixed parts of the colon (ascending and descending colon), and images of nine lesions in 12 lesions (75%) were well synchronized in the unfixed part of the intestine in Crohn's disease patients. Conclusion: Real‐time virtual sonography significantly reduced the examination time of intestinal US. Intestinal RVS can help the ultrasonographer to guide the US probe to detect and monitor intestinal lesions by synchronizing reference images, especially in inflammatory bowel disease patients (UMIN Clinical Trials Registry number: UMIN000011571).